Religion-Based Law Enforcement in Indonesia, Malaysia, and Saudi Arabia: A Comparative Law Analysis - Mohammad Furqoon Senoaji; Ifahda Pratama Hapsari (JUSTISI, 2025)
This study aims to analyze and compare the complexity of religious law's implications for law enforcement in Indonesia, Malaysia, and Saudi Arabia, which have a majority Muslim population. The study comprehensively analyzed the literature, maximizing articles and sources relevant to the three countries' patterns, differences and similarities of law enforcement, by summarizing and examining the writings. A comprehensive method is used by outlining legal reforms and public education to ensure that equal rights for religious minorities are substantially respected and protected. This novelty is in the results from previous studies that examined the application of Islamic criminal law in Indonesia, Malaysia, and Saudi Arabia. The results of this study show the complex challenges and potential for protecting the rights of minority citizens in implementing Islamic law in each of these countries. Furthermore, it is mentioned in this study that the linear application of Islamic law in state policy often leads to tensions and resistance between religious principles, human rights principles and internationally recognized law which is currently often accepted by Saudi Arabia through the ijtihad system and the dual influence of Sharia and regulations issued by the state. In contrast, Indonesia and Malaysia are considered more flexible by applying two legal systems for Islamic communities and civil society in general. The study concluded by comparing law enforcement activities carried out in the three countries, which revealed why the three countries with the majority of the population of Islam could implement a legal system with diverse impacts.